A passive communication based islanding detection technique for AC microgrid. (May 2022) - Nale, Ruchita; Biswal, Monalisa; Kishor, Nand
Highlights: Islanding detection in microgrid. Communication based passive islanding detection technique. Phase angle difference information of superimposed impedance. Multiple distributed energy resources. Selectivity, dependability and security test. Abstract: This paper presents a secured communication based passive anti-islanding technique, using phase angle difference information of superimposed impedance computed at both distributed generation (DG) and point of common coupling (PCC) ends. In the approach, the PCC end signal information is transmitted every cycle to DG sites to analyze the event, hence more effective and reliable. The performance of the method is evaluated for different test conditions such as low power mismatch islanding events, different fault types and switching events. A standard distribution system model is considered and simulated in EMTDC/PSCAD. Additionally, islanding detection is also performed on experimental signals obtained on PV system integrated with grid emulator. The complete procedure is presented, and performances are evaluated by conducting selectivity, dependability and security tests.